2016
DOI: 10.1136/bmjopen-2016-012938
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus conservative treatment for lumbar disc herniation: a prospective cohort study

Abstract: ObjectivesEvidence comparing the effectiveness of surgical and conservative treatment of symptomatic lumbar disc herniation is controversial. We sought to compare short-term and long-term effectiveness of surgical and conservative treatment in sciatica symptom severity and quality of life in patients with lumbar disc herniation in a routine clinical setting.MethodsA prospective cohort study of a routine clinical practice registry consisting of 370 patients. Outcome measures were the North American Spine Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 38 publications
6
129
0
10
Order By: Relevance
“…Gugliotta et al recently demonstrated equivalent medium-and long-term outcomes for conservative and surgical treatment of LDH [47]. However, other studies have also demonstrated improved 1-and 2-year outcomes in the surgical treated group when compared to conservatively managed patients.…”
Section: Treatment Non-operativementioning
confidence: 96%
“…Gugliotta et al recently demonstrated equivalent medium-and long-term outcomes for conservative and surgical treatment of LDH [47]. However, other studies have also demonstrated improved 1-and 2-year outcomes in the surgical treated group when compared to conservatively managed patients.…”
Section: Treatment Non-operativementioning
confidence: 96%
“…The so fare latest study came in autumn 2016, when Gugliotta et al presented a cohort study on 370 routinely treated patients, without randomization and with 20% non-surgically treated [62]. Even in this study surgery showed to be better up to three months, but not thereafter.…”
Section: Treatment Optionsmentioning
confidence: 92%
“…Lifetime incidence of having a symptomatic lumbar disc herniation, is a more uncertain calculation, but Frymoyer found between 13-40% 1992 [59] and Gugliotta et al 30%, in a recent paper [62].…”
Section: Epidemiologymentioning
confidence: 99%
“…1 , Шульга А.Н. 1 , Зорин Н.Н. 2 Цель: улучшить результаты хирургического лечения поясничных болевых синдромов и радикулопатии, вызванных многоуровневым смещением межпозвонковых дисков пояснично-крестцового отдела позвоночника.…”
Section: хирургическая тактика при многоуровневых смещениях поясничныunclassified
“…Вступ У хворих із поперековим болем та радикулопатією одночасне зміщення двох і більше поперекових міжхребцевих дисків (ПМХД) явище не рідкісне [1]. За даними авторів, багаторівневе зміщення ПМХД трапляється в 38-56 % випадків [2,3].…”
Section: к л ю ч е в ы е с л о в а : м е ж п о з в о н к о в ы й д иunclassified